Sistem Pendukung Keputusan Penerima Bantuan Covid-19 Menggunakan Metode Simple Additive Weighting (SAW) - Simanullang, Rahma Yuni; Melisa, Melisa; Mesran, Mesran (TIN: Terapan Informatika Nusantara, 2021)
This study aims to determine the acceptance of covid19 assistance. The COVID 19 pandemic is devastating, resulting in a lot of unemployment. The poverty rate is increasing, and there are also cases of rampant mortality, the mobility of the community itself and security insecurity. With that, the government plans to provide special assistance for people who cannot afford to face the COVID 19 pandemic. The distribution of social assistance as a realization of the social safety net program during the COVID 19 pandemic has worried many homeworkers, starting from reduced income, setting targets to distribution. However, the mechanism for distributing aid often becomes very complicated, or the nominal amount decreases and there is often an inaccurate point of view because the criteria for beneficiaries do not match the data that is inaccurate / does not match the reality in the field, resulting in misunderstandings between the community. In essence, the Simple Additive Weighting (SAW) method is often known as the weighted method. The basic concept of the Simple Additive Weighthing (SAW) method is to find the weighted sum of the performance branches for each alternative on all criteria. The Simple Additive Weighting (SAW) method requires a decision matrix normalization process. So the author uses the Simple Additive Weighting method or it is often said with the term SAW. To solve this problem, namely by using one of the methods to obtain a multiple and complete assessment of criteria with a conferential thinking framework to carry out hierarchical considerations, then calculate the weight of each criterion to determine the priority recommendations for receiving COVID 19 assistance according to the data. On the results of this study.